2018
DOI: 10.1108/jec-01-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Cultural values as determinants of entrepreneurial intentions among university students in Cape Town-South Africa

Abstract: Purpose This paper aims to determine how cultural values (language and religion) impact on entrepreneurial intentions of students at the University of Cape Town, University of Stellenbosch University of the Western Cape and Cape Peninsula University of Technology. Design/methodology/approach This empirical study was conducted under mixed-methods approach, using survey-correlational strategy. Primary data were collected from a sample of 278 students. A questionnaire survey was used to collect data which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The biggest increase was seen in the answers to question C2-"Culture in my country is highly favorable to entrepreneurial activity", with an increase of 0.63 pp in the average response before and during the pandemic. Our results are in line with the ones by Van Trang, Do and Loan [74] that indicated that "social status", self-respect, and culture [75,76] contribute to increased entrepreneurial intent. Culture in turn increases motivation, which in turn increases entrepreneurial intent [44].…”
Section: Results Presentation and Discussionsupporting
confidence: 92%
“…The biggest increase was seen in the answers to question C2-"Culture in my country is highly favorable to entrepreneurial activity", with an increase of 0.63 pp in the average response before and during the pandemic. Our results are in line with the ones by Van Trang, Do and Loan [74] that indicated that "social status", self-respect, and culture [75,76] contribute to increased entrepreneurial intent. Culture in turn increases motivation, which in turn increases entrepreneurial intent [44].…”
Section: Results Presentation and Discussionsupporting
confidence: 92%
“…They conclude that people who have high "intrinsic" religiosity tend to choose self-employment rather than being employed by other as they have more chance to actualize their values toward others. On the contrary, based on the empirical study in South Africa, Kalitanyi and Bbenkele (2018) did not find the influence of student's religiosity on the entrepreneurial intentions. Basu and Altinay (2002) conclude that ethnic minorities in the UK have more incentives to become an entrepreneur compared with white counterparts.…”
Section: The Impact Of Religiosity On the Entrepreneurshipmentioning
confidence: 78%
“…However, knowledge of entrepreneurial support did not have a significant effect on entrepreneurial intention. Again, by examining the impact of cultural values on entrepreneurial intentions of University students in four South African universities, Kalitanyi and Bbenkele (2018) found that language as a cultural variable influences entrepreneurial intentions whereas religion was not found to do so.…”
Section: Opportunity Vs Necessity Entrepreneurshipmentioning
confidence: 99%